A system dynamic framework for identifying demand gaps in Indian processed food sector. (24th March 2014) - Mahajan, Rajneesh; Garg, Suresh; Sharma, P.B.
The objective of this research paper is to study the dynamics behind the capacity enhancement and demand surges in the Indian Processed Food Sector (PFS). An attempt has been made to identify and analyse variables that lead to a gap between fresh food and processed food demands. A dynamic model of processed food is presented in the form of casual loop using System Dynamics (SD) approach. The major outcome of the paper is the identification of the variables, the gap between fresh and processed food demands. A demand and production capacity model of PFS is proposed. The proposed model will help in analysing the future scenario of PFS. It will be beneficial for processed food manufacturers, policy makers, PFS corporate and food researchers.